Properties of Ground-State of 17,19,20,24,26F using the Wave Functions of Harmonic-Oscillator and Spherical Hankel Functions - Khalaf, Saif Ali J. (Iraqi Journal of Science, 2023)
The nuclear size radii, density distributions and elastic electron scattering charge form factors for Fluorine isotopes (17,19,20,24,26F) were studied using the radial wave functions (WF) of harmonic-oscillator (HO) potential and free mean field described by spherical Hankel functions (SHF) for the core and the valence parts, respectively for all aforementioned isotopes. The parameters for HO potential (size parameter ) and SHF were chosen to regenerate the available experimental size radii. It was found that using spherical Hankel functions in our work improved the calculated results quantities in comparison with empirical data.